2015
DOI: 10.1007/s13187-015-0798-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality Oncology Practice Initiative (QOPI) Measure Adherence Between Oncology Fellows, Advanced Practice Providers, and Attending Physicians

Abstract: Quality improvement measures are uniformly applied to all oncology providers, regardless of their roles. Little is known about differences in adherence to these measures between oncology fellows, advance practice providers (APP), and attending physicians. We investigated conformance across Quality Oncology Practice Initiative (QOPI) measures for oncology fellows, advance practice providers, and attending physicians at the Durham Veterans Affairs Medical Center (DVAMC). Using data collected from the Spring 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…15 An oncology fellow–led project used QOPI as part of a QI project to improve opioid-associated constipation from a baseline of 52% compliance to 92%. 16 Zhu et al 17 demonstrated that informing oncology fellows, attending physicians, and advanced practice providers about QOPI process measures in iterative QI cycles improved the consistency of care among the various providers. QOPI can enable practices to conduct QI through self-examination, with the overarching goals of improving patient care and creating a QI culture.…”
Section: Introductionmentioning
confidence: 99%
“…15 An oncology fellow–led project used QOPI as part of a QI project to improve opioid-associated constipation from a baseline of 52% compliance to 92%. 16 Zhu et al 17 demonstrated that informing oncology fellows, attending physicians, and advanced practice providers about QOPI process measures in iterative QI cycles improved the consistency of care among the various providers. QOPI can enable practices to conduct QI through self-examination, with the overarching goals of improving patient care and creating a QI culture.…”
Section: Introductionmentioning
confidence: 99%